(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
In the article, the need for a new approach to assessing the efficiency of commercial banks and improving it based on the new requirements of interbank competition under the conditions of institutional changes in the banking system, and the main directions are researched. The advantages and specific features of the system of using the system of evaluating the efficiency of commercial banks, which is used by international rating agencies, according to the instructions of the Central Bank of the Republic of Uzbekistan, have been scientifically substantiated. Possibilities of its application in the activity of commercial banks of the Republic of Uzbekistan were studied and recommendations were developed.